Agreement Between Automated and Human Measurements of Heart Rate in Patients With Atrial Fibrillation. Issue 5 (September 2018) - Lin, Ting-Tse; Wang, Chia-Ling; Liao, Min-Tsun; Lai, Chao-Lun
Abstract : Background: The accuracy of heart rate (HR) measurement by automated blood pressure monitors in patients with atrial fibrillation (AF) remains unclear. The authors investigate the agreement between HR measurements by 2 automated devices and human counting in patients with AF. Methods: In 47 patients with persistent AF, HR was recorded using 2 automated blood pressure monitors: Omron M5-I and Microlife BPA100 Plus. Human counting of HR by a stethoscope was used as the reference. For each method, 3 readings were made and the mean was calculated for comparison. In addition to Wilcoxon signed rank test, the correlation between HR measurements by automated devices and human counting was determined using Spearman's rank correlation coefficient ( r ), and the agreement between HR measurements by both devices and human counting was validated by the Bland-Altman plot and intraclass correlation coefficient (ICC). Results: Overall, we found no significant difference in HR measurements between devices and human counting (Omron vs human counting, 81.1 ± 11.1 vs 80.2 ± 10.8 beats per minute [bpm]; P = .21, r = 0.911; ICC, 0.954; Microlife vs human counting, 81.3 ± 10.8 vs 80.2 ± 10.8 bpm; P = .22, r = 0.842; ICC, 0.912). However, in patients with HR greater than 80 bpm, the HR measured by the Microlife device was significantly higher than that measured by human counting (91.1 ± 5.2 vs 87.1 ± 8.6 bpm, P = .034). Conclusion: There was a high agreement between HR measurements by 2 automated devices and human counting, but the Microlife device may overestimate HR in AF patients with HR greater than 80 bpm.